2012
DOI: 10.1177/0363546512437334
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound as a Primary Evaluation Tool of Bone Stress Injuries in Elite Track and Field Athletes

Abstract: Therapeutic ultrasound is a reproducible procedure that is reliable to diagnose bone stress injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
46
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 23 publications
1
46
0
Order By: Relevance
“…A stress fracture grading system using therapeutic ultrasound (TUS) by detecting pain over the site of stress fracture was proposed by Romani and colleagues [15] and Papalada and colleagues [16] recently reported positive results in their cohort study involving 113 elite track and field athletes. However, recent systematic review and metaanalysis by Schneiders and colleagues [17] showed a pooled sensitivity of 64 %, a specificity of 63 %, and a positive likelihood of 2.1.…”
Section: Classification and Grading Of Stress Fracturesmentioning
confidence: 99%
“…A stress fracture grading system using therapeutic ultrasound (TUS) by detecting pain over the site of stress fracture was proposed by Romani and colleagues [15] and Papalada and colleagues [16] recently reported positive results in their cohort study involving 113 elite track and field athletes. However, recent systematic review and metaanalysis by Schneiders and colleagues [17] showed a pooled sensitivity of 64 %, a specificity of 63 %, and a positive likelihood of 2.1.…”
Section: Classification and Grading Of Stress Fracturesmentioning
confidence: 99%
“…19 Computed tomography (CT) is useful and specific when a fracture line exists, but this occurs at the late stage of a bone stress injury. 18 Ultrasound has been used to assess bone stress injuries in track and field athletes, with a reported sensitivity of 81.9% and specificity of 66.6% compared with magnetic resonance imaging (MRI), 45 but further studies are needed to assess the use of ultrasound as a method of screening.…”
mentioning
confidence: 99%
“…CT scanning can show the severity of the stress reaction, especially the signs that precede an actual cortical fracture, such as osteopenia, resorption cavities and striation; however, these signs are extraordinarily subtle 10. In older fractures, CT can also provide information about union versus non-union fractures and can show periosteal reaction, which is an indicator of healing 7.…”
Section: Imagingmentioning
confidence: 99%
“…First, highly motivated athletes tend to train through pain, choosing not to interrupt training for recovery or rehabilitation 9 10. In such athletes, using imaging to diagnose or exclude early stress injuries can be an effective tool in persuading them to stop training and allow time for recovery or even to continue training where no stress injury is found 10. A second challenge is that these injuries are frequently misdiagnosed as other conditions, such as intercostal muscle strain 4 6 16.…”
mentioning
confidence: 99%